Strong expression of FOXP1 identifies a distinct subset of diffuse large B-cell lymphoma (DLBCL) patients with poor outcome. - Barrans, S; Fenton, J; Banham, A; Owen, R; Jack, A (2004)
FOXP1 (Forkhead box-P1) is a winged-helix transcription factor that is differentially expressed in resting and activated B cells. FOXP1 expression has been demonstrated in a subset of diffuse large B-cell lymphomas (DLBCLs) and is more common in the nongerminal center (non-GC), activated B-cell type; however, its prognostic significance is uncertain. We analyzed presentation lymph nodes from 126 patients with nodal DLBCL, previously classified according to GC and BCL2 status, for FOXP1 protein expression using standard immunocytochemistry. Uniform high FOXP1 expression was demonstrated in 23 of 126 patients with DLBCL. This high level of expression was almost exclusively confined to patients who lacked the GC phenotype, who expressed MUM-1 and BCL2 in the absence of t(14; 18), and who were identified as a subgroup of patients with particularly poor outcomes in a group with already poor prognoses. The data presented suggest that high FOXP1 expression is an independent prognostic factor in DLBCL.